OPTIMALISASI BUMDES DALAM UPAYA MENDORONG EKONOMI DESA - Syaifudin, Rizal (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this community service is to encourage the optimization of village-owned enterprisesof Tunas Mulya, Jiput Village, Jiput District, Pandeglang Regency in order to improve the villageeconomy. Tunas Mulya village-owned enterprises have some business fields including the productionof “Nyai Jiput” rice and money transfer service through BRILink. However, the village-ownedenterprises of Tunas Mulya still have problems such as has not a business feasibility study document,limitted on capital participation, limited on human resources, threat of crop failure, andinternetnetwork trouble during transaction. Hence, this community service focuses to givecounseling forvillage-owned enterprises management such as conduct training in order to make financial reportsand business feasibility study reports. Some sugestions from this community service are that village-owned enterprises of Tunas Mulya can develop their business products, especially in the field offisheries, increase its strengthen and expandcooperation network, then provide stimulus to localresidents to attract their participation.